1998
DOI: 10.1038/bjc.1998.203
|View full text |Cite
|
Sign up to set email alerts
|

Putative markers for the detection of breast carcinoma cells in blood

Abstract: Summary The aim of this study was to investigate certain genes for their suitability as molecular markers for detection of breast carcinoma cells using the reverse transcriptase-polymerase chain reaction (RT-PCR). RNA was prepared from MCF-7 breast carcinoma cells and peripheral blood leucocytes of healthy female volunteers. This RNA was screened for mRNA of MUC1, cytokeratin 19 (CK19) and CD44 (exons 8-11) by RT-PCR and the results validated by Southern blots. Variable degrees of expression of MUC1 and CD44 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 27 publications
3
20
1
Order By: Relevance
“…Two previous reports have suggested MUC-1 to be tissue specific (Noguchi et al, 1994(Noguchi et al, , 1996a; however, there is no reported data on the number of control patients, and a total of only ten lymph nodes assessed. Our results concur with that of other groups in showing that MUC-1 is expressed in cells of lymphohaemopoetic origin (Hoon et al, 1995;Eltahir et al, 1998). Several studies in breast cancer have reported K19 to be a tissue-specific marker (Datta et al, 1994;Schoenfeld et al, 1994Schoenfeld et al, , 1996Schoenfeld et al, , 1997Noguchi et al, 1996a;Eltahir et al, 1998;Lockett et al, 1998).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Two previous reports have suggested MUC-1 to be tissue specific (Noguchi et al, 1994(Noguchi et al, , 1996a; however, there is no reported data on the number of control patients, and a total of only ten lymph nodes assessed. Our results concur with that of other groups in showing that MUC-1 is expressed in cells of lymphohaemopoetic origin (Hoon et al, 1995;Eltahir et al, 1998). Several studies in breast cancer have reported K19 to be a tissue-specific marker (Datta et al, 1994;Schoenfeld et al, 1994Schoenfeld et al, , 1996Schoenfeld et al, , 1997Noguchi et al, 1996a;Eltahir et al, 1998;Lockett et al, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…However, data from studies assessing the detection of disease in colon and lung cancer have raised questions with regard to the tissue specificity of these markers (Adams et al, 1995;Burchill et al, 1995;Hoon et al, 1995;Krismann et al, 1995;Denis et al, 1997;Dingemans et al, 1997;Eltahir et al, 1998) CEA gene expression must be regarded with caution as a tumour specific marker, as it has been detected by nested RT-PCR in normal tissues. Jonas et al (1996) found 23% of controls without cancer had evidence of CEA expression in peripheral blood, which the authors propose may be due to venepuncture-induced skin contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…muc-1 and her2͞neu have also been reported as useful markers for breast cancer in some blood studies (4, 18) but not others (19,20). Our results found muc-1 high in normal blood and hence not a useful marker (Fig.…”
Section: High-sensitivity Array Screening Of Candidate Markers In Bloodcontrasting
confidence: 32%
“…This high rate of false positivity might be caused primarily by the high sensitivity of the nested RT-PCR assay picking up illegitimate low-level expression of CK-19 in mononuclear blood cells (Chelly et al, 1989;Eltahir et al, 1998;Schoenfeld et al, 1994). So far, EGF-R-specific transcripts have not been detected in human blood mononuclear cells.…”
Section: Figurementioning
confidence: 98%